Cost-Utility Analysis (CUA) dalam Pengambilan Keputusan Kesehatan: Sebuah Tinjauan Literatur dan Analisis Kebijakan - Lismardani Lismardani; Eko Khair Anthony; Eka Yan Fitri; Budi Hartono; Alfani Ghutsa Daud (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing cost of healthcare services, limited resources, and growing demand for high-quality care require rational and evidence-based decision-making approaches. One of the most widely used economic evaluation methods in health policy is Cost-Utility Analysis (CUA), which assesses the efficiency of health interventions by comparing costs and outcomes measured in quality-adjusted life years (QALYs). This study aims to systematically review the concepts, methods, and applications of CUA in health policy decision-making, as well as to identify its benefits, limitations, and implementation challenges. A systematic literature review was conducted following the PRISMA guidelines. Relevant articles published between 2019 and 2025 were retrieved from PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. Eligible studies were analyzed thematically and synthesized narratively. The findings indicate that CUA is widely applied in the evaluation of health technologies, service delivery models, preventive programs, and population-based strategies, and plays a key role within the Health Technology Assessment (HTA) framework. The use of QALYs enables comprehensive comparisons across diseases and populations. However, several challenges remain, including limited availability of local utility data, methodological variability, and ethical and equity-related concerns. In conclusion, CUA serves as a strategic tool for supporting efficient and transparent health policy decision-making. Nevertheless, it should be used as a complementary instrument alongside ethical and social considerations to ensure fair and sustainable health policies.